2000
DOI: 10.1002/(sici)1097-0274(200001)37:1<75::aid-ajim7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of chronic work-related musculoskeletal disorders of the distal upper extremity

Abstract: This clinical review will describe the epidemiology, clinical presentation, and management of the following work‐related musculoskeletal disorders (WMSDs) of the distal upper extremity: deQuervain's disease, extensor and flexor forearm tendinitis/tendinosis, lateral and medial epicondylitis, cubital tunnel syndrome, and hand‐arm vibration syndrome (HAVS). These conditions were selected for review either because they were among the most common WMSDs among patients attending the New York State Occupational Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
86
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 59 publications
3
86
0
2
Order By: Relevance
“…This is consistent with the epidemiological literature (4,12,13,26,27). The higher risk of DQD among women could reflect both biological predispositions (sex effect) and greater exposure to biomechanical repetitive work-related constraints (gender-effect) (28).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 90%
“…This is consistent with the epidemiological literature (4,12,13,26,27). The higher risk of DQD among women could reflect both biological predispositions (sex effect) and greater exposure to biomechanical repetitive work-related constraints (gender-effect) (28).…”
Section: Petit Le Manac'h Et Alsupporting
confidence: 90%
“…While some authors (2) consider ulnar nerve entrapment at the elbow difficult to diagnose, even with EMG, definitions based on symptoms and signs are available for epidemiologic studies (2,3). Nonetheless, as Bozentka (4) mentioned in his physiological study of this disorder, epidemiologic studies of occupational ulnar nerve entrapment at the elbow are rare (4).…”
mentioning
confidence: 99%
“…Pathologic changes have also been described in the digital tuft mechanoreceptors (Pacinian corpuscles) and among myelinated digital fibres. 1 Physical characteristics of exposure that appear to play a role in the development of HAVS include the type of vibration (frequency, amplitude and direction), the vibratory force and impulse type, the cumulative hours of exposure, the intermittency of exposure, the state of tool maintenance and a cold environment. 2 Biodynamic factors such as the grip force required to use the tool, the operator's control of the tool and the surface area of the tool handle, as well as factors such as the patient's medical history of injury, susceptibility and protective practices also play a role (www .ccohs.ca/oshanswers/phys_agents /vibration/vibration_effects.html #_1_3).…”
mentioning
confidence: 99%
“…Plethysmography before and after cold provocation is the laboratory test accepted for evaluating vascular manifestations of HAVS by the Stockholm Hand-arm Committee. 1 Additional tests include digital thermometry at baseline and after cold-water immersion and Doppler blood pressure and flow measurement. However, a recent review of the diagnostics of vascular symptoms concluded that taking a good patient history was the best method for diagnosing blanched fingers triggered by cold.…”
mentioning
confidence: 99%
See 1 more Smart Citation